Vijsʹkovoslužbovci Vermachtu u spryjnjatti nacelennja okupovanogo Donbasu (za materialamy usnoistoryčnych džerel) - Penter, Tanja; Tytarenko, Dmytro (Schid, 2018)
This article highlights the peculiarities of the perception of German soldiers by the population of Donbass who survived the Nazi occupation. The study is based on material including more than 90 interviews with witnesses of the occupation conducted by the authors during the period of 2001-2018. The article throws light on the following issues: features of everyday life of the ordinary people during the war, the problems of perception of the occupation and the occupiers and the specific of relations with the German military. Furthermore, the article deals with the peculiarities of the practice of conducting the interviews, the degree of their representativeness and the value as a historical source.In a first step the authors analyze the formation of the image of the Germans before the occupation. It becomes clear that in addition to official propaganda factors like the experience of communication with the Germans during the First World War and the German occupation of 1918 also played a significant role in the formation of the perception of the Germans. On basis of the analyzed interview material the main practices of interaction between the local population and occupiers are characterized. Finally, the paper also explores the specific nature of the perception of the satellites of Germany’s troops and the local collaborators. Special attention is paid to the factors which influenced the narratives of respondents who survived the Second World War, with focus on the context of the military conflict in Donbas in 2014-2018. The authors conclude that oral history sources reflect different, especially regionally disparate versions of historical memory. They acquire paramount importance in the context of political pressure on history and attempts to create a single unified and ideologically framed version of history.
Gesehen am 26.01.2026